The Effect of Day Lighting Transmittance Through Window on Indoor Air Temperature - Le, Norsyalmieza; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2021)
This study reviewed the recent studies of the application of external shading device on its effect to reduce heat on indoor condition while providing appropriate level of illuminance. Further analysis was conducted to investigate the relationship between indoor air temperature and illuminance level. The data collections involve two main phases where the first phase is by systematic review for both survey and field measurement types of studies. While the second phase focused on data abstraction and analysis. About 20 selected papers were reviewed and finally 5 screened papers were used extensively for analysis. Based on the analysis, it was found that by introduction of the external venetian blinds with at least 40° of slat angle can produce heat reduction by 8 °C. Meanwhile, illuminance and solar radiation rate can be reduced by up to 376 lx and 21 W/mm² respectively. The relationship analysis shows that there was a moderate to strong correlation between the indoor air temperature and illuminance level (R=0.96 to R=0.55). It is important to find the optimization balance between natural lighting and temperature gain.